Endovascular management in children with vein of Galen aneurysmal malformation - S. Pongpech (2018)
Background: A vein of Galen aneurysmal malformation (VGAM) is a relatively rare vascular malformation, often resulting in high morbidity and mortality. While surgical arterial clipping has been reported for decades, results in the literature have recently favored endovascular treatment. Methods: During a 10-year period, all children who were diagnosed with VGAM were included in our follow-up study. Clinical and radiological records of 5 consecutive patients were reviewed. Results: 5 children (4 infants and 1 child) who suffered from symptoms caused by VGAM were treated by means of transarterial embolization with n-butyl cyanoacrylate (NBCA) alone. Their age at the time of diagnosis ranged from 4 months to 3 years. 4 of the 5 patients presented with macrocranium, and 3 of those 4 patients were infants. The fifth patient presented with seizures. None of the patients presented with hemorrhage. 2 of the 5 VGAM patients were classified as the mural type, while the others 3 were of the choroidal type. Both mural type patients achieved total obliteration of lesions with good outcomes. One of the remaining 3 patients exhibited autistic behavior during late follow-up, whereas the other 2 had good outcomes. 2 patients suffered from asymptomatic ruptured arterial feeders during embolization, which were treated immediately with glue embolization. Conclusion: Our purpose in treating a patient with VGAM is to achieve normal brain development using minimally invasive interventions. Our treatment strategies were influenced by each patient's clinical status, their ages, and varying radiographic features. We achieved considerable successful in treating our patients by means of transarterial embolization alone. © Georg Thieme Verlag KG Stuttgart - New York.